تحليل فعالية الوسائل التعليم اللغة العربية باستخدام لعبة كويزيز (QUIZIZZ) في ترقية المهارة الكتابة - Farihatun Farihatun; Muhammad Nu’man (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
In learning Arabic languange, learning media is a very important element to achieve learning objectives. Arabic languange teachers use the media a lot as a tool to provide learning materials to student or as a tool to explain the results of assessments during student learning. One of the learning media that is widely is an online learning medium in the form of a game. The purpose of this reaserch is to describe of effectiveness oh using Quizizz as a medium for learning Arabic languange in the form of game to improve reading skills. This reaserch was conducted with ualitative descriptive approach uing the literature study methode, namly by analyzing different conceptual information from various sources. The results of this study indicate that Quizizz as an online learning medium in the form of a game is a medium that can be used very easily, effectively and interestingly in learning Arabic language to improve reading skills. In addition, thins learning media can be used direcly or in the form if assignments.